Bone morphogenetic protein Smads signaling in mesenchymal stem cells affected by osteoinductive calcium phosphate ceramics. Issue 3 (9th June 2014) - Tang, Zhurong; Wang, Zhe; Qing, Fangzhu; Ni, Yilu; Fan, Yujiang; Tan, Yanfei; Zhang, Xingdong
Abstract Porous calcium phosphate ceramics (CaP ceramics) could induce ectopic bone formation which was regulated by various signal molecules. In this work, bone marrow mesenchymal stem cells (MSCs) were cultured on the surface of osteoinductive hydroxyapatite (HA) and biphasic calcium phosphate (BCP) ceramics in comparison with control (culture plate) for up to 14 days to detect the signal molecules which might be affected by the CaP ceramics. Without adding osteogenic factors, MSCs cultured on HA and BCP both expressed higher Runx2, Osterix, collagen type I, osteopontin, bone sialoprotein, and osteocalcin at various stages compared with control, thus confirmed the osteoblastic differentiation of MSCs. Later study demonstrated the messenger RNA level of bone morphogenetic protein 2 (BMP2) and BMP4 were also significantly enhanced by HA and BCP. Furthermore, Smad1, 4, 5, and Dlx5, the main molecules in the BMP/Smads signaling pathway, were upregulated by HA and BCP. Moreover, the higher expression of Smads and BMP2, 4 in BCP over HA, corresponded to the better performance of BCP in stimulating in vitro osteoblastic differentiation of MSCs. This was in accordance with the better osteoinductivity of BCP over HA in vivo. Altogether, these results implied that the CaP ceramics may initiate the osteoblastic differentiation of MSCs by influencing the expression of molecules in BMP/Smads pathway. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1001–1010, 2015.